The Effect of Motivation and Competence on Employee Performance with Job Satisfaction as a Mediating Variable (Case Study at The Cidadap District Office of Bandung City) - Firma Agustin Dwi Admaja; Salsa Billa Putri Yuningsih; Gurawan Dayona Ismail; Nunung Ayu Sofiati; Riyandi Nur Sumawidjaja (Dinasti Publisher, 2025)
This study aims to analyze the influence of motivation and competence on employee performance directly and indirectly through job satisfaction as a mediating variable at the Cidadap Subdistrict Office in Bandung City. The research employs a quantitative approach and utilizes survey data collected from 52 employees through structured questionnaires measured on a Likert scale. Data analysis is conducted using Structural Equation Modeling with Partial Least Squares (SEM-PLS) to evaluate measurement validity, reliability, and the hypothesized relationships. The findings reveal that motivation significantly affects employee performance both directly and through job satisfaction. Competence influences job satisfaction positively and substantially but does not have a direct significant impact on performance. Job satisfaction serves as a critical mediator enhancing the relationship between motivation and competence toward performance. The results highlight that fostering motivation and developing competence with supportive job satisfaction mechanisms are essential strategies for improving employee outcomes in public sector institutions. This research provides practical implications for management in promoting effective human resource development and enhancing service quality in local government offices.